A Study on driving forces behind the successful deworming in Korea - Park, Ji-yeun (KDI School, 2011)
Nowadays, deworming is an urgent issue in many developing countries. This is largely because parasitic diseases threaten people in that they adversely affect the proper functioning of organs and can even take a human life, even slowing down further economic progress while weakening human capital. To this day, it is generally accepted idea that there is causal relationship between economic progress and deworming. In other words, as capita per income increases, sanitation and hygiene levels are improved, which in turn lower parasite infection rate. In this respect, the case of Korea’s deworming is unique because Korea completed its deworming program in the late 1970s at a time when Korea was still an impoverished country with a per capita income of just US $ 1,729. It means that deworming in Korea was not a result of its economic progress. Then, how could Korea eradicate parasitic diseases in a very short period of time regardless of its poor economic conditions? Foreign aid played a significant role in launching deworming project. More importantly, Korea had improved sanitation conditions through the New Village Movement in the early 1970. The New Village Movement ignited the general public’s desire for environmental cleanup by providing incentives based on merit-based approach. On top of that, under the strong governmental ownership, Korea could effectively allocate limited resources into the New Village Movement, and it maximized deworming impacts dramatically. Furthermore, it has been found that deworming had significantly positive impacts on public health in Korea.
Thesis(Master) --KDI School:Master of Public Policy,2011